Microlearning: A Bibliometric Analysis of Research Trends from 2002 to 2023 - Raissa Mochamad (Journal of Computers for Science and Mathematics Learning, 2024)
Microlearning is a highly efficient method of teaching that provides learners with focused, and brief learning. It offers learners more understandable and effective information by reducing complex topics into smaller, more easily understood parts. Microlearning is a new method of learning design that can improve learning ability. This study of the current status and trends of microlearning research was conducted with comprehensive bibliometric analysis over the period 2002-2023. Using quantitative methods to analyse the trend in microlearning and VOSviewer to identify relationship mapping between variables. Overall, 459 relevant publications from the Scopus database have been identified between 2002 to 2023. The results show that publications on microlearning are increasing. The most frequently occurring keywords in articles about microlearning are “microlearning”, “e-learning” and “micro-learning”. The two most cited papers as references were written by Schewn in 2003 and Edge in 2011. The top three authors who have published in microlearning are from the University of Wollongong; the most prolific institution is the University of Wollongong. Lecture Notes in Computer Science published by Springer; the United States is the most prolific country.